LEVERS OF INCREASING REGIONAL REVENUE IN BITUNG CITY, NORTH SULAWESI PROVINCE, INDONESIA - Aisyah, Siti; Juniadi, Dedy; Pangemanan, Audy; Setiani, Made Yudhi; Nurhayati, Syafiqoh; Yandes, Jufri (Department of Government, FISIP, Universitas Padjadjaran, 2024)
This study aims to explore levers for increasing regional revenues. The problem in this study is how regional autonomy can increase regional income and the possibility of developing regional income potential while regions have limited resources. This study is the result of a qualitative study. The research location is in Bitung City, North Sulawesi Province. Data collection was conducted through interviews with selected stakeholders. With purposive sampling techniques and direct observation at the research site. Data analysis is done through coincidences: data reduction, data presentation, coding, data conceptualization, and conclusions/verification. The findings of this study are that three levers play a role in the success of increasing regional revenues, primarily provincial taxes, namely digitization of taxpayer data, the part of business knowledge transfer in taxation, and grouping potential local taxes. Digitalization of taxpayers is carried out to facilitate tax administration and supervise tax collection. Transferring knowledge about the business is needed to improve the general circulation of money. With more and more people trying and increasing quality in doing business, it will increase the circulation of money in society. Meanwhile, grouping potential taxes is needed to map revenue targets through taxes to be right on target. The implication of this study is a follow-up study on making a predictive model of local tax revenue, taking into account the characteristics of the local economy.gb777